Social media features, perceived group norms, and adolescents’ active social media use matter for perceived friendship quality - Angelini, Federica; Gini, Gianluca; Marino, Claudia; Van Den Eijnden, Regina (Frontiers in Psychology, 2024)
Developmental researchers are becoming increasingly interested in the role of social media in adolescents’ experiences with their peers; however, to date, few studies have investigated the association between youngsters’ interactions with friends online and the perceived quality of their friendship relationships. Thus, the current study aims to test the associations between three social media features, as perceived by adolescents, (i.e., availability, quantifiability, visualness) and the quality of adolescents’ friendships (in terms of perceived validation, intimacy, companionship), considering participants’ frequency of active social media use (i.e., self-oriented and other-oriented social media use), and the role of perceived group norms about social media use. Moreover, we tested potential differences across gender groups. Participants were 751 adolescents (Mage=16.2, SD = 1.5). A SEM analysis showed that, among the perceived social media features, availability was positively associated with perceived friendship quality–both directly and indirectly. Furthermore, friends who participated more in other-oriented social media use reported being more satisfied with their friendship relationships and the results showed that peer influence processes were also active on social media. Taken together, these results emphasize the study of social media as a social context for a better understanding of contemporary peer experiences during adolescence. Specifically, novel behaviors (e.g., liking or commenting on posts or content of peers), which characterize interactions between friends, may support relational functioning and well-being purposes in both the offline and online context.